Homologous Recombination Assay for Interstrand Cross-Link Repair - Nakanishi, Koji (2011)
DNA interstrand cross-links (ICLs) covalently link both strands of the DNA duplex, impeding cellular processes like DNA replication. Homologous recombination (HR) is considered to be a major pathway for the repair of ICLs in mammalian cells as mutants for HR components are highly sensitive to DNA-damaging agents that cause ICLs. This chapter describes GFP assays to measure HR following site-specific ICL formation with psoralen through DNA triplex technology. This approach can be used to determine the genetic requirements for ICL-induced HR in relation to those involved in HR repair of other DNA lesions such as double-strand breaks.